2021
DOI: 10.3390/w13243636
|View full text |Cite
|
Sign up to set email alerts
|

Future Climate Change Impact on the Nyabugogo Catchment Water Balance in Rwanda

Abstract: Droughts and floods are common in tropical regions, including Rwanda, and are likely to be aggravated by climate change. Consequently, assessing the effects of climate change on hydrological systems has become critical. The goal of this study is to analyze the impact of climate change on the water balance in the Nyabugogo catchment by downscaling 10 global climate models (GCMs) from CMIP6 using the inverse distance weighting (IDW) method. To apply climate change signals under the Shared Socioeconomic Pathways … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 80 publications
(96 reference statements)
0
2
0
Order By: Relevance
“…Besides, referring to Umugwaneza et al [ 80 ], a study conducted on average annual discharge in the same basin, the study reported a 3.26% increase in 2020–2050 and a 4.53% decline in 2050–2100 under ssp585. However, the study used neither statistical nor dynamic bias correction technique but used IDW in downscaling or interpolating precipitation to a desired station, which should still give out the mother model resolution output as fine as 25–50 km for RCMs and more than 111 km for GCMs [ 81 ].…”
Section: Resultsmentioning
confidence: 91%
“…Besides, referring to Umugwaneza et al [ 80 ], a study conducted on average annual discharge in the same basin, the study reported a 3.26% increase in 2020–2050 and a 4.53% decline in 2050–2100 under ssp585. However, the study used neither statistical nor dynamic bias correction technique but used IDW in downscaling or interpolating precipitation to a desired station, which should still give out the mother model resolution output as fine as 25–50 km for RCMs and more than 111 km for GCMs [ 81 ].…”
Section: Resultsmentioning
confidence: 91%
“…Rwanda relies heavily on agriculture for economic development and food security. However, it faces climate change risks that could disrupt its climatic conditions, thereby impacting agricultural productivity [13]. The potential outcomes, such as higher temperatures, intense rainfall, and prolonged dry spells, pose a threat to crops, livestock, soil, water, and biodiversity elements crucial for the well-being of Rwandans, particularly the poor and vulnerable [14].…”
Section: Introductionmentioning
confidence: 99%